Peran regulasi diri belajar terhadap flow akademik pada mahasiswa yang sedang mengerjakan skripsi - Nurfadhilah Reziani Usman; Lukman -; Nur Akmal (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Abstract: Students often face various obstacles while working on their thesis, which can give them feelings of anxiety, stress, fatigue, boredom, and a sense of being stuck. These negative emotions experienced by students indicate a lack of academic flow during the thesis writing process. This study aims to determine the role of self-regulated learning in academic flow among students who are working on their thesis. The respondents in this study are 201 students who are currently undertaking their thesis in the Faculty of Psychology, Universitas Negeri Makassar. The sampling technique used is simple random sampling, with a simple linear regression hypothesis test. The data on self-regulated learning are collected using the Motivated Strategies for Learning Questionnaire scale developed by Pintrich, Smith, Garcia, and McKeachie (1991) and adapted by the author. The data on academic flow are collected using the Flow Inventory for Student scale created by Yuwanto (2011) and adapted by the author. Based on the analysis, it is found that there is a significant role of self-regulated learning in academic flow. The R-square value of 0.361 indicates that 36.1% of the variance in academic flow can be explained by self-regulated learning. This suggests that higher levels of self-regulated learning are associated with higher levels of academic flow, while lower levels of self-regulated learning are associated with lower levels of academic flow. The implications of this study call for educational institutions to pay attention to students' ability to self-regulate their learning in order to enhance their academic performance.Keywords: academic flow; self-regulated learning; student